2019
DOI: 10.1002/qj.3581
|View full text |Cite
|
Sign up to set email alerts
|

Persistent precipitation extremes in the Yangtze River Valley prolonged by opportune configuration among atmospheric teleconnections

Abstract: This study investigates whether and how three synoptic-scale teleconnections, i.e. East Asia/Pacific teleconnection (EAP), Silk-Road teleconnection (SR) and Eurasia teleconnection (EU), induce persistent precipitation extremes (PPEs) in the Yangtze River Valley. Results show that only the EAP teleconnection has the potential of independently incurring PPEs; while the other two teleconnections' influences on PPEs need to be exerted via their liaison with the EAP pattern. Cases are accordingly grouped into two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…Previous studies have noted that the eastward‐shifted and enhanced SAH favors summer precipitation over SWC on an interannual time scale (D. Chen et al., 2016) and over the Sichuan Basin on a subseasonal time scale (Ge & Ren, 2019). Previous research reported that more extreme precipitation occurs over the Yangtze River Valley with eastward‐extended intensified SAH (Y. Chen & Zhai, 2015, 2016; Y. Chen, Zhai, et al., 2019; Ning et al., 2017). Our study verifies the influence of the SAH on extreme precipitation over SWC at a synoptic scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have noted that the eastward‐shifted and enhanced SAH favors summer precipitation over SWC on an interannual time scale (D. Chen et al., 2016) and over the Sichuan Basin on a subseasonal time scale (Ge & Ren, 2019). Previous research reported that more extreme precipitation occurs over the Yangtze River Valley with eastward‐extended intensified SAH (Y. Chen & Zhai, 2015, 2016; Y. Chen, Zhai, et al., 2019; Ning et al., 2017). Our study verifies the influence of the SAH on extreme precipitation over SWC at a synoptic scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous research reported that more extreme precipitation occurs over the Yangtze River Valley with eastward-extended intensified SAH (Y. Chen & Zhai, 2015Y. Chen, Zhai, et al, 2019;Ning et al, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Precipitation and temperature (or dry and hot events) during summer in China have been shown to be associated with different atmospheric processes. The summer rainfall in western and northern China is closely related to the westerlies while that in eastern China is mainly affected by water vapor transport from the ocean (e.g., the Bay of Bengal, South China Sea, and western Pacific) associated with East Asia Summer Monsoon (EASM), which is related to the Western Pacific Subtropical High (WPSH), East Asian westerly jet (EAWJ), and South Asian High (SAH) (Y. Chen et al., 2019; W. Huang et al., 2015; Linderholm et al., 2011; Q. Sun et al., 2017; W. Wang et al., 2015; W. Wei et al., 2015; L. X. Zhang & Zhou, 2015; Zhu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This spatial distribution of ‘positive–negative–positive’ height anomalies largely resembles the mid‐ to high‐latitude sections of the Pacific‐East Asian teleconnection pattern (Huang and Li, 1988), which controls weather and climate in China, but with a more northerly displacement. Such anomalies of large‐scale circulations tend to be relatively stable (Chen et al ., 2019), which is conducive to sustaining high temperatures and, therefore, to producing compound hot extreme events.…”
Section: Resultsmentioning
confidence: 99%
“…The dispersed energy stimulates disturbances over mid‐lower reaches of the Yangtze River, which subsequently extracts barotropic and baroclinic energy from the background mean flow (the subtropical westerly jet). Regions atop mid‐lower reaches of the Yangtze River are known as a hotspot for disturbance–flow interactions (Chen et al ., 2019). In particular, baroclinic energy conversion is more efficient in maintaining the anomalous anticyclone (disturbances), favouring its persistence through day and night and even over a period of several days.…”
Section: Resultsmentioning
confidence: 99%